Respuesta :
Answer:
Given the system of equation:
2x+3y=3 ......[1]
y=8-3x ......[2]
as per the given condition;
Substitute the value of y from the equation [2] into the [1] equation;
[tex]2x+3(8-3x) =3[/tex]
Using distributive property on LHS, (i.e, [tex]a\cdot(b+c) = a\cdot b+ a\cdot c[/tex] )
[tex]2x+3\cdot 8+ 3 \cdot (-3x) =3[/tex] or
2x+24-9x =3
Combine like terms;
[tex]-7x+24 =3[/tex]
Subtract 24 from both the sides,
[tex]-7x+24-24=3-24[/tex]
Simplify:
-7x =-21
Divide by -7 to both sides of an equation;
[tex]\frac{-7x}{-7} = \frac{-21}{-7}[/tex]
Simplify:
x =3
Substitute the value of x =3 in equation [2] to solve for y;
[tex]y=8-3(3) =8 -9 =-1[/tex]
Hence, the answer for this question is:
The resulting equation is: [tex]2x+3(8-3x) =3[/tex]
And the value of x =3 and that of y = -1
The value of x =3 and that of y = -1.
Given the system of equations:
2x+3y=3 ......[1]
y=8-3x ......[2]
as per the given condition;
Substitute the value of y from the equation [2] into the [1] equation;
[tex]2x+3(8-3x)=3[/tex]
Using distributive property on LHS,
What is the distributive property?
[tex]a(b+c)=ab+ac[/tex]
[tex]2x+24-9x =3[/tex]
Combine like terms;
[tex]-7x+21=0[/tex]
Subtract 24 from both the sides,
Simplify
-7x =-21
Divide by -7 to both sides of an equation
x =3
Substitute the value of x =3 in equation [2] to solve for y;
y=8-3(3)
y=8-9
y=-1
Hence, the answer to this question is:
[tex]2x+3(8-3x)=3[/tex]
The resulting equation is: [tex]2x+3(8-3x)=3[/tex]
And the value of x =3 and that of y = -1.
To learn more about the equation visit:
https://brainly.com/question/2972832
#SPJ5